Analisis Pendapatan dan Faktor- Faktor yang Mempengaruhi Produksi Usahatani Padi Sawah Varietas Mustajab di Kecamatan Indrapuri Kabupaten Aceh Besar - Nadia; Sri Fitri; Diah Eka Puspita (Departemen Agribisnis, Fakultas Pertanian, Universitas Syiah Kuala associated with AAI (Asosiasi Agribisnis Indonesia). Jl. Tgk. Hasan Krueng Kalee No. 3, Kopelma Darussalam, Banda Aceh, 23111, Indonesia. Email: agrisep@usk.ac.id, 2026)
Rice isn’t just a staple food in Indonesia it’s a big player in the country’s economy. The Mustajab variety stands out as a top choice, developed from local Jember rice using plant breeding technology from BATAN. Farmers like it because it helps them earn more. This study set out to look at two things: how much income farmers actually get from growing Mustajab rice, and how factors like land size, seed use, labor, fertilizers, and pesticides shape its production in Indrapuri Regency. Researchers used a survey, picking 22 Mustajab rice farmers at random, which made up about 30% of the area’s growers. For income, they used a simple formula: profit equals total revenue minus total costs. To figure out what affects production, they ran a multiple linear regression based on the Cobb-Douglas Production Function, tweaking it with natural logarithms. On average, farmers earned IDR 13,790,534 from growing Mustajab rice. That’s a solid number it shows the crop pays off and makes sense to keep cultivating. When looking at the stats, the F-test showed that land area, fertilizers seeds, labor, and pesticides all make a real difference to how much Mustajab rice gets produced. In other words, these factors matter, and the numbers back it up. The study also ran a partial test, but that part got cut off here.